La migración venezolana y sus efectos en el desarrollo social de los habitantes de la Ciudadela Velasco Ibarra de Machala. - Jiménez Sánchez, Andre Danny; Tandazo Chimbo, Alisson Nayely (Machala: Universidad Técnica de Machala, 2023)
Currently, Venezuelan migration has left a profound mark on the Velasco Ibarra neighborhood of Machala, Ecuador. This phenomenon has transformed not only the demographics of the area, but also its social and economic fabric. The main objective of this study is to determine the effects of Venezuelan migration on the social development of the inhabitants of the Velasco Ibarra neighborhood. To achieve this objective, specific objectives were established that include the characterization of migration, the exploration of local perception about the migrants and the identification of mechanisms for improving the coexistence and the social cohesion. Venezuelan migration to the Velasco Ibarra neighborhood has been characterized for being a phenomenon mainly familiar, with a diversity in the composition of the families and a varied socio-cultural adaptation. The migrants have moved due to reasons economic, politic and social, and have faced challenges significant that include discrimination and vulnerabilities economic and legal. Although engaged in diverse occupations, many of them experience forms of precarious labor. This diversity in the experiences of the migrants has delineated a community in process of adaptation, balancing their cultural roots with the integration in their new environment. The perception of the inhabitants locals towards the Venezuelan migration in the neighborhood Velasco Ibarra is diverse and nuanced. While some concerns about negative behaviors, such the intimidation and the consumption of substances, are evident, also there are positive and balanced views that value the contribution and enrichment of the migrants. Contrary to the hypothesis of a mostly negative perception, the data reveal a reality complex and not uniform. This underscores the need to address these results with a broad and contextual approach. sociocultural projects as a strategy with the potential to overcome existing barriers and promote cohesion in the community. These cultural events will reflect the diversity of traditions, customs, and values present in the community, offering opportunities for intercultural dialogue and the forging of friendships. Furthermore, spaces for meetings and learning will be created through workshops, presentations, and participatory activities. Values of respect, tolerance, and solidarity will be promoted, and efforts will be made to build a shared sense of belonging to the community. This proposal also seeks to strengthen the positive image of the Velasco Ibarra neighborhood, recognizing it as a space where diversity is valued and where coexistence and collaboration are fundamental.
Actualmente, la migración venezolana ha dejado una profunda huella en la ciudadela Velasco Ibarra de Machala, Ecuador. Este fenómeno ha transformado no solo la demografía del área, sino también su tejido social y económico. El objetivo principal de este estudio es determinar los efectos de la migración venezolana en el desarrollo social de los habitantes de la ciudadela Velasco Ibarra. Para alcanzar este objetivo, se establecieron objetivos específicos que incluyen la caracterización de la migración, la exploración de la percepción local sobre los migrantes y la identificación de mecanismos para mejorar la convivencia y la cohesión social. La migración venezolana hacia la ciudadela Velasco Ibarra se ha caracterizado por ser un fenómeno principalmente familiar, con una diversidad en la composición de las familias y una adaptación sociocultural variada. Los migrantes se han desplazado debido a razones económicas, políticas y sociales, y han enfrentado desafíos significativos que incluyen discriminación y vulnerabilidades económicas y legales. Aunque participan en diversas ocupaciones, muchos de ellos experimentan formas de precariedad laboral. Esta diversidad en las experiencias de los migrantes ha delineado una comunidad en proceso de adaptación, equilibrando sus raíces culturales con la integración en su nuevo entorno. La percepción de los habitantes locales hacia la migración venezolana en la ciudadela Velasco Ibarra es diversa y matizada. Si bien algunas preocupaciones sobre comportamientos negativos, como la intimidación y el consumo de sustancias, son evidentes, también existen visiones positivas y equilibradas que valoran la contribución y el enriquecimiento de los migrantes. Contrario a la hipótesis de una percepción mayoritariamente negativa, los datos revelan una realidad compleja y no uniforme. Esto subraya la necesidad de abordar estos resultados con un enfoque amplio y contextual.
Keywords: MIGRACION VENEZOLANA; DESARROLLO SOCIAL; CONVIVENCIA; COHESION SOCIAL